Legal Analysis of Implementation Justice Collaborators in The Indonesian Criminal Justice System in Corruption Criminal Acts (Study of Decision No. 110 K/Pid.Sus/2024) - Tyara Dhali Allfia; Diana Setiawati (Proceeding International Conference Restructuring and Transforming Law, 2026)
Introduction: Corruption as an extraordinary crime requires innovative law enforcement strategies, one of which is through justice collaborators, namely perpetrators who work together to uncover other, more dominant perpetrators. In Indonesia, the regulation has been accommodated in various legal instruments, but its implementation still faces obstacles in the form of unclear criteria and inconsistencies in the granting of legal awards. This study uses a normative juridical method with a descriptive analytical approach through a literature study of regulations, doctrines, and court decisions as well as case studies that focus on court decisions. The focus of the study is to analyze the judge's considerations in Decision Number 110 K/Pid.Sus/2024 and the legal consequences of including criminal acts based on Article 55 paragraph (1) of the Criminal Code. The results of the study indicate that the application of justice collaborators is inconsistent. Cooperative defendants are not explicitly recognized as justice collaborators and instead receive increased criminal sentences at the cassation level. This reflects the gap between norms and practice. Therefore, strengthening regulations and clearer guidelines are needed so that their implementation guarantees justice, certainty, and legal benefits.